THE INCIDENCE AND PREVALENCE OF RHEUMATIC DISEASES IN RUSSIA IN 2012–2013 - R. M. Balabanova; Sh. F. Erdes (Научно-практическая ревматология, 2015)
The incidence of major rheumatic diseases was analyzed inRussia's adult population  in 2012–2013 on the basis of the statistical reports of the Ministry of Health ofRussia(Form No. 12).Among the adult population  ofRussia, the overall incidence of acute rheumatic fever (ARF) decreased by 11.6% (from 1666 to 1474 cases). No case of ARF was registered in 11 of the 83 subjects of the Federation in 2013. The inci- dence rates per 100,000 adult population  compared toRussia's ones were higher in theRepublicofIngushetia(21.0%), theChechen Republic(13.2%), and the Chukotka Autonomous District (26.2%). All cases of ARF were first notified. The overall incidence rates of chronic rheumatic heart diseases amongRussia's adult population  tend to reduce slightly [by 5.3% (from 182,286 to 172,687 cases)].In the period in question, the total number of patients with musculoskeletal diseases (MSD)  slightly rose. The bulk of rheumatic  patients from the MSD group are more than 4 million patients with osteoarthritis  (OA), half of them (2,454,563) being those who are older than able-bodied  age. The incidence of OA tends to increase in all Federal Districts (FD).  The most common  joint inflammatory diseases are rheumatoid  arthritis (RA) (286,000 cases), spondylopathies  (90,000 cases), and osteoporosis (152,000 cases). The incidence rates of MSD per 100,000 adult population  are higher in the North-Western (19,397.7), Volga (16,552.6), and Siberian (16,133.4) FD thanRussia's mean rate (14,205.5). There were somewhat higher incidence rates of RA per 100,000 population  in 2013 than in 2012 (241.4 and 245.6, respectively). The rates in the North-Western, Ural, Far Eastern, and Volga FDs are higher than the mean Russian ones.In 2011, the rubric of «Ankylosing spondylitis» (AS) was replaced by that of «Spondylopathies» that, besides AS (ICD-10 M45), encompasses other inflammatory spondylopathies  (M46), including infectious one, which does not allow single out the spinal inflammatory diseases under a rheumatologist's  competence. InRussia, there were 39,800 patients with AS in 2010 and as many as 89,000 patients with spondylopathies  in 2013.The incidence of systemic connective tissue diseases (SCTD)  remains rather stable. Unfortunately, SCTDs include different nosological entities (sys- temic lupus erythematosus, systemic sclerosis, systemic vasculitides, etc.), which cannot refine trends in the incidence of specific diseases.In a number of the Federation's  subjects, the incidence rate of reactive arthritis (ReA) is higher thanRussia's mean one. It is not inconceivable that not only arthropathies caused by prior enteric and urogenital infection are taken as ReA, leading to the hyperdiagnosis of ReA.The incidence of osteoporosis varies in FDs: from 226.5 per 100,000 adult population  in the Siberian FD to52.0 inthe Southern  FD,  which is most likely to be associated with the fact that an instrumental  examination  cannot be made in patients to detect this pathology.DOI: http://dx.doi.org/10.14412/1995-4484-2015-120-124